Analysis of the Algebraic Reasoning Ability of State Madrasah Tsanawiyah Students in Solving Mathematical Problems based on Cognitive Style - Pradana Putra, Firnanda; Toni, Toni (Universitas Islam Ahmad Dahlan (UIAD), 2024)
This article aims to describe the algebraic reasoning abilities of state Islamic boarding school students in solving mathematical problems based on a reflective and impulsive style. This research uses a qualitative type because it observes and narrates the phenomena and symptoms that students have. The triangulation used is technical triangulation through interviews, observations, and documents such as cognitive tests (MFFT) and algebraic reasoning material tests. The interviews used are structured based on indicators of algebraic reasoning, namely understanding problems, making generalizations, creating general forms or formulas, and solving problems or carrying out general forms. The results show that students with a reflective cognitive style can understand arithmetic sequences and series material well, carry out generalizations by generating letter symbols and making standard formulas, and carry out calculations correctly and provide conclusions. This is different from impulsive cognitive students, students tend not to come up with letter symbols when making generalizations, students immediately use ready-made formulas and carry out calculations with correct results, and do not provide conclusions